PROTECTION OF UNCERTIFIED WAQF LAND ASSETS: THE PERSPECTIVE OF LAW NUMBER 41 OF 2004 CONCERNING WAQF (STUDY OF BATU BARA REGENCY) - Dewi Lestari; Syafruddin Syam (Journal Analytica Islamica, 2025)
This paper raises the issue of legal protection for uncertified waqf land assets in Batu Bara Regency. Uncertified waqf land has the potential to cause disputes and misuse due to the lack of formal legal force. Waqf land assets are objects that have high economic value for someone who is given by a certain person to another. Waqf land assets have a value that can provide for a person's life when given, but become problematic when they have not been legally legalized through a certificate. These uncertified waqf land assets are still common among the community, especially in Batu Bara Regency. In Batu Bara Regency, there are several uncertified waqf land assets. Based on data obtained from the Ministry of Religious Affairs of North Sumatra Province in 2025 in Batu Bara Regency, it is known that there are a total of 594 waqf land assets. Of this total, there are 327 certified waqf land assets and 267 uncertified waqf land assets. Thus, there are still problems regarding uncertified waqf land assets. Therefore, this study aims to analyze the objective conditions of waqf land asset protection in Batu Bara Regency, how is the protection of uncertified waqf land assets according to the perspective of Law Number 41 of 2004 concerning Waqf in Batu Bara Regency and the factors causing uncertified waqf land assets in Batu Bara Regency. The research method used by the researcher in this journal article is a qualitative research method with an analytical descriptive approach. Data collection in this study uses primary data and secondary data. The primary data used by the researcher is by going directly to the field through observation and interviews, while the secondary data carried out by the researcher is by using books, journal articles and supporting documents. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the protection of uncertified waqf land assets in Batu Bara Regency based on the perspective of Law Number 41 of 2004 concerning waqf is The objective condition of waqf land assets in Batu Bara Regency can be seen through its management. Waqf land assets are used for the benefit of humanity such as the construction of prayer rooms, mosques, cemeteries, schools and others. Waqf land that does not yet have a certificate in Batu Bara can be proven by the Waqf Pledge Deed (AIW) and the Waqf Pledge Deed Replacement Deed (APAIW) issued by the Waqf Pledge Deed Making Official (PPAIW). The factors causing uncertified waqf land assets in Batu Bara Regency are the low public understanding of the urgency of waqf land certification, complex administrative procedures, and high costs that must be incurred.